ANALISIS DESKRIPSI DISPOSISI PRODUKTIF SISWA PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI GENDER - Miftahul Fallah (Universitas Bhinneka PGRI, 2024)
Productive disposition is the tendency, attitude, or mental state of a person towards a thing or situation. For example, in mathematics, students' attitudes and tendencies towards mathematics, such as belief in the value of mathematics, motivation in learning mathematics, or confidence in their ability to understand mathematical concepts. This study aims to describe students' productive disposition in learning mathematics in terms of gender. This research uses quantitative descriptive data analysis with survey method. This research was conducted on class X students in 30 students divided into 15 males and 15 females of SMAN 5 West Karawang selected through purposive sampling method. The data collection technique used was the distribution of a productive disposition questionnaire consisting of 20 statements and measuring against seven indicators. The results showed that productive disposition in mathematics learning was in the good category with a percentage of 52%, this was supported by the amount of activeness of female students 27% compared to male students who were only 25%.